DEVELOPING LISTENING AND SPEAKING SKILLS IN PSYCHOLOGY: ACADEMIC LISTENING, CRITICAL THINKING, AND PROFESSIONAL COMMUNICATION (INSTRUCTIONAL AND METHODOLOGICAL GUIDELINES) - Mykolaichuk, Alisa (European Science, 2025)
This monograph presents an integrated instructional and methodological framework for developing academic listening, critical thinking, and professional speaking skills among first-year psychology students studying through ESP and CLIL approaches. Grounded